Peran Pengetahuan dan Sikap dalam Mewujudkan Kepatuhan Perawat terhadap Pemilahan Sampah Medis - Budirman Budirman; Ain Khaer; Rafidah Rafidah; Nurul Yani Aksan (Buletin Keslingmas, 2026)
Hospitals generate medical solid waste that has the potential to pollute the environment and pose health risks. At Andi Makkasau Regional General Hospital Parepare, the mixing of infectious and non infectious waste is still observed despite the average generation of medical waste reaching 3 tons per month. This study aimed to analyze the relationship between nurses’ knowledge and attitudes and their compliance with medical waste segregation practices. A cross sectional study design was employed involving 51 nurses from the Anggrek and Nusa Indah wards selected through total sampling. Data were collected through questionnaires, observations, and direct interviews and analyzed using the chi square test. The results showed that 35 respondents (68.6%) were compliant with medical waste segregation practices. Most respondents had good knowledge (70.6%) and positive attitudes (84.3%). There was a significant relationship between knowledge and compliance (p = 0.012), as well as between attitude and compliance (p = 0.013). Knowledge and attitude were significantly associated with nurses’ compliance with medical waste segregation practices. Hospitals are encouraged to conduct regular training and supervision programs to improve nurses’ compliance with medical waste segregation procedures.